2016
DOI: 10.1016/j.ejps.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and shadowgraph imaging of cocrystal dissolution and assessment of in vitro antimicrobial activity for sulfadimidine/4-aminosalicylic acid cocrystals

Abstract: Purpose: The aim of this work was to evaluate the influence of crystal habit on the dissolution and in vitro antibacterial and anitiprotozoal activity of sulfadimidine:4-aminosalicylic acid cocrystals.Methods: Cocrystals were produced via milling or solvent mediated processes. In vitro dissolution was carried out in the flow-through apparatus, with shadowgraph imaging and mechanistic mathematical models used to observe and simulate particle dissolution. In vitro activity was tested using agar diffusion assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Grossjohann et al used liquidassisted milling and spray drying to generate two different polymorphic forms of sulfadimidine:4-aminosalicylic acid cocrystals (1:1) where spray drying from ethanol led to the formation of the metastable form II of the cocrystal and liquid (ethanol)-assisted milling led to the formation of the thermodynamically stable form I of the cocrystal. Spray drying was determined, by PXRD and DVS to lead to partial amorphisation, which was not observed for form II cocrystals prepared by liquidassisted milling or solvent evaporation from ethanol or acetone [147]. Alhalaweh and Velaga showed that spray drying of incongruently saturating systems can lead to the formation of pure cocrystals.…”
Section: Role Of Manufacturing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grossjohann et al used liquidassisted milling and spray drying to generate two different polymorphic forms of sulfadimidine:4-aminosalicylic acid cocrystals (1:1) where spray drying from ethanol led to the formation of the metastable form II of the cocrystal and liquid (ethanol)-assisted milling led to the formation of the thermodynamically stable form I of the cocrystal. Spray drying was determined, by PXRD and DVS to lead to partial amorphisation, which was not observed for form II cocrystals prepared by liquidassisted milling or solvent evaporation from ethanol or acetone [147]. Alhalaweh and Velaga showed that spray drying of incongruently saturating systems can lead to the formation of pure cocrystals.…”
Section: Role Of Manufacturing Methodsmentioning
confidence: 99%
“…DVS is important for studying the relationship between sorbed vapors and different solid forms [202]. Sorption-desorption isotherms in dynamic vapor sorption may be used to quantify the equilibrium amount of vapor sorbed or desorbed as a function of the amount of vapor present, at isothermal/ isobaric conditions [147]. The vapors can be from water or any volatile solvent.…”
Section: Dynamic Vapor Sorptionmentioning
confidence: 99%
“…The coformer should be a GRAS (generally regarded as safe) listed molecule with high solubility, but it can be also be another active molecule that enhances the activity of the API. Several examples are described in the literature where the coformer improves API activity such as the sulfadimidine (SDM) -4 aminosalicylic acid (4ASA) cocrystal for infectious diseases [6,7] or the celecoxib -tramadol (hydrochloride) cocrystal which is used for the treatment of pain, and was recently approved and commercialized by Esteve S.A [8,9].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…In a hypothetical situation, a change in flow rate should not impact the relative fluid velocity, however, the effect of flow rate on dispersion of the powder bed and particle interactions with the cell surfaces will be affected by flow rate. Shadowgraph imaging has proven useful for exploring particle behavior within the FTC apparatus in terms of particle velocities, sizes, and particle agglomeration tendencies (4,14).…”
Section: Flow-through Dissolution Apparatusmentioning
confidence: 99%
“…Shadowgraph imaging is a noninvasive optical technique which, in addition to quantifying the size and shape of particles at a point in time, can also quantify their absolute velocity ( Figure 1) (4,14). Digital images of particle-laden fluid are captured against a background of pulsed light.…”
Section: Shadowgraph Imagingmentioning
confidence: 99%